Glycoproteins composed of major surface immunodeterminants of Pneumocystis carinii. - Tanabe, K (1989)
Pneumocystis carinii is a pathogen which causes fatal pneumonia in patients with acquired immune deficiency syndrome. To facilitate the basic study of P. carinii, we analyzed the major surface proteins by immunochemical and biochemical methods. The major protein components of both cysts (resting form) and trophozoites (vegetative form) are part of a group of proteins called P115 with apparent masses of 105 to 120 kilodaltons. They represent an unusually large portion of the total proteins of this organism. The purified proteins exhibited six isoelectric variants when analyzed by two-dimensional gel electrophoresis. A monoclonal antibody raised against cysts recognized all six variants and reacted with epitopes that were located in the cell wall, thereby indicating that P115 is an immunoreactive surface component. Data are presented that the isoelectric variants contain identical or closely related protein components and that they are mannose-rich glycoproteins. Deglycosylated P115 migrates primarily as a single more acidic protein in two-dimensional gels, suggesting that the isoelectric variants may be due primarily to differences in glycosylation. The majority of sera tested from humans with diagnosed pneumocystosis reacted strongly with the P115 proteins.